PENGALAMAN LANSIA DALAM MENJALANI MASA PENSIUN DI DESA LAUT DENDANG KECAMATAN PERCUT SEI TUAN KABUPATEN DELI SERDANG - Gea, Roselina Riska Putri; Simatupang, Lenny Lusia (STIKes Mitra Husada Medan, 2024)
Background Retirement is a normal period that every working person goes through and a period where various aspects of a person's life experience changes and are handled as early as possible in order to prevent the development of psychosocial problems. The aim of this research is to describe the experience of the elderly in retirement in Laud Dendang Village. Precut Sei Tuan District, Deli Serdang Regency. This research method is qualitative research. Data collection techniques were carried out using interview guidelines, observation and documentation, in Laut Dendang Village, Percut Sei Tuan District, Deli Serdang Regency, this research was conducted in April 2024 and there were 8 informants who were found using purposive sampling. Data analysis techniques are carried out using data reduction, data display and drawing conclusions. Conclusion: The results of the research show that the experience of the elderly in undergoing retirement in Laut Dendang Village, Percut Sei Tuan District, Deli Serdang Regency, from eight informants, 3 themes were obtained: 1) Efforts to improve the health of the elderly in retirement are carried out by maintaining movement activities, namely by continuing to move so that they remain healthy. get fit, then adopt a healthy lifestyle by limiting food and drink, then get enough rest by reducing intense activities outside the home, and finally carry out routine health checks by checking up with the nearest doctor or midwife. 2) The activities of the elderly in retirement are doing side jobs such as selling, raising livestock and also farming. This is done so that the elderly can survive and not become a burden on their families. Then some elderly people choose to rest at home because they are sick and some have received pension funds, some don't work anymore and just stay at home and the elderly spend time with their families. Because family support is what the elderly need. 3) Complaints from the elderly after retirement are physical complaints such as starting to get sick, the body gets tired easily, heart disease, high blood pressure, gout and difficulty in walking. Psychological complaints felt by the elderly after retirement include feelings of anxiety and uselessness, sadness and fear because the body is no longer able to carry out activities.